Implementasi Sistem Akademik Berbasis Web di SD Anak Aptana Bangsa Jakarta Timur - Rasiban; Bening Sari Purnomo; Beatrice Yrain; Arjun Fricco; Febryan Bayu Pratama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
This outreach aims to introduce a web-based academic information system at SD Anak Aptana Bangsa East Jakarta to be a beneficial activity that serves the needs of the school. In this activity, through the development of a website-based information system, we will provide a platform with a database for managing data on students, faculty and staff at schools and information on academic activities. This activity involves SD Anak Aptana Bangsa teachers and staff to fulfill the requirements of the STIKOM CKI KKP Strata-1 course. The programming language PHP and the database MySQL are used for the development of this information system. This information system provides an information medium that makes it easier for teachers and students to obtain information about school activities. In addition, the system will also serve as a promotional tool for SD Anak Aptana Bangsa in East Jakarta. By introducing a web-based academic information system at SD Anak Aptana Bangsa, the outreach is expected to bring real benefits in increasing the efficiency of academic data and information management in schools.